Validity of the technology acceptance model (TAM) : A sensemaking perspective - Aafaqi, Bushra; Jantan, Muhamad; Ramayah, T. (Universiti Utara Malaysia, 2007)
This study investigates whether sensemaking activities influence technology acceptance and if the strength of relationship between TAM’s constructs changes over a period of time. This study was a panel-based longitudinal study, whereby data was collected in three stages within a single semester. The setting of the study was at the School of Management, USM. The major findings of the study showed that sensemaking does influence the TAM if activities are undertaken at high and low levels and also sensemaking influences individual constructs of TAM rather than the whole model. This study failed to prove that there is a significant change in the strength of relationship between TAM constructs over a period of time under sensemaking influence, which is that sensemaking activities were found not to exhibit any moderation effect on the TAM constructs. Sensemaking acts as an external variable which influences TAM rather than moderate the strength of the relationship between TAM constructs. This could be because the technology in question was mandatory to be used by the subjects rather than voluntary. Implications for managers are discussed.